Evaluation of some factors affecting the risk of kidney damage in patients with hypertension - Gharishvandi, Fatemeh; Kazerouni, Faranak; Rahimipour, Ali; Nasiri, Malihe (Archives of Advances in Biosciences, 2014)
Chronic kidney disease (CKD) is an increasing cause of morbidity and mortality worldwide. Prospective data on risk factors for CKD are few. Hypertension is one of the risk factors for CKD. In the past serum creatinine concentration was used as marker of kidney function but it proffers a late reflection of reduced glomerular filtration rate(GFR), which limits its ability to detect impaired kidney function. Cystatin C and NGAL have recently been proven useful to quantitate CKD. Therefore in this study, we assessed the effect of some risk factors on reduction of estimated glomerular filtration rate (eGFR) in patients with high blood pressure. This study was performed on 42 hypertensive patients and 30 healthy volunteers, both with normal serum creatinine and urea concentration. In this study, we measured serum cystatin C and Plasma NGAL. Serum creatinine and urea levels of the patients were measured after an overnight fasting. . Estimated glomerular filtration rate (eGFR) was considered as the gold standard method .Serum cystatin C and plasma NGAL were measured using commercially available human ELISA kits. Logistic regression and T-test were used for statistical analysis. The results of logistic regression showed that among the variables studied, plasma levels of NGAL, age and duration of hypertension were significantly associated with the eGFR<78(P<0.05). Our findings suggest that, increased levels of NGAL, age and duration of hypertension predicts a higher odds of impaired renal function